Insulin Analogs and Cancer - Sciacca, Laura; Le Moli, Rosario; Vigneri, Riccardo (Frontiers in Endocrinology, 2012)
Today, insulin analogs are used in millions of diabetic patients. Insulin analogs have been developed to achieve more physiological insulin replacement in terms of time course of the effect. Modifications in the amino acid sequence of the insulin molecule change the pharmacokinetics and pharmacodynamics of the analogs in respect to human insulin. However, these changes can also modify the molecular and biological effects of the analogs. The rapid-acting insulin analogs, lispro, aspart and glulisine, have a rapid onset and shorter duration of action. The long-acting insulin analogs glargine and detemir have a protracted duration of action and a relatively smooth serum concentration profile. Insulin and its analogs may function as growth factors and therefore have a theoretical potential to promote tumor proliferation. A major question is whether analogs have an increased mitogenic activity in respect to insulin. These ligands can promote cell proliferation through many mechanisms like the prolonged stimulation of the insulin receptor, stimulation of the IGF-1 receptor (IGF-1R), prevalent activation of the ERK rather than the AKT intracellular post-receptor pathways. Studies on in vitro models indicate that short-acting analogs elicit molecular and biological effects that are similar to those of insulin. In contrast, long-acting analogs behave differently. Although not all data are homogeneous, both glargine and detemir have been found to have a decreased binding to IR but an increased binding to IGF-1R, a prevalent activation of the ERK pathway, and an increased mitogenic effect in respect to insulin. Recent retrospective epidemiological clinical studies have suggested that treatment with long-acting analogs (specifically glargine) may increase the relative risk for cancer. Results are controversial and methodologically weak. Therefore prospective clinical studies are needed to evaluate the possible tumor growth-promoting effects of these insulin analogs.